A framework of cloud service selection based on trust mechanism. (2017) - Yang, Yuli; Peng, Xinguang; Fu, Donglai
Customers always face the challenge to choose the appropriate cloud service, which can satisfy their different quality of service (QoS) requirements. Because traditional methods could not quantify the security of cloud services effectively, a novel method was proposed to quantify it. In the proposed method, the definition of trust was given in the context of cloud service selection, and the trust mechanism based on cloud model theory was adopted to quantify the security of cloud services. Taking trust, cost and time into account, we put forward a multi-QoS-aware cloud service selection strategy, and employed the analytic hierarchy process (AHP) method to help the cloud customer to select the appropriate cloud service. Compared with traditional methods, the proposed method is sensitive to the change of the security. It can provide a simple and effective decision-making method for cloud customers.